Produksi Infografik Dinamis Zona Afotik Berjudul Ekosistem Gelap Gulita - Syah, Nurhbalisyah; Apriaji, Muhammad Yusuf; Fauzie, Mochamad (Perkumpulan Program Studi Film dan Televisi Indonesia, 2024)
The research aims to produce dynamic infographic of the aphotic zone entitled Pitch Dark Ecosystem. The aphotic zone is a region without sunlight that covers the entire ecosystem in the deep sea. The aphotic zone holds so many mysteries that it attracts the attention of scientists to explore it further. Unfortunately, public interest in knowledge of the deep sea is limited, even still not much compared to knowledge about outer space. One of the reasons is the lack of media that raises the theme of the deep sea, especially those designed for teenagers. This research offers a design solution by designing dynamic infographics. The type of research is qualitative research, especially the qualitative descriptive type. The data collected is knowledge of aphotic zones, which consists of sea depth zoning, environmental conditions, and survival strategies of deep-sea creatures. The data source consists of literature and resource persons (marine experts). The data collection techniques include literature studies and interviews. The data collected is then selected and formulated into a dynamic infographic. The research has produced dynamic infographics that are the characteristics of late adolescence, with characteristics, including The infographics using a flat design illustration drawing style with bright analog color composition, the use of an informal Poppins typeface, and a dynamic layout style. This dynamic infographic targets behavioral changes in late adolescents and more curiosity to seek knowledge of the deep-sea aphotic zone